Концепція реформування системи управління охороною праці - Пронюк, О. Д. (ХНУРЕ, 2019)
The need to reform the labor protection management system in Ukraine is explored in given work. The European experience in the management of occupational safety and human resources is analyzed. The necessity of transition to preventive safety management methods, focus on risk management objectives are researched